The Use of Dual Antiplatelet Therapy in Acute Coronary Syndrome and Percutaneous Coronary Intervention - A. S. Tereshchenko; E. V. Merkulov; A. N. Samko; S. A. Abugov (Столичная издательская компания, 2019)
Currently, cardiovascular diseases play a leading role in the structure of morbidity. It is expected that by 2020 in developing countries cardiovascular diseases will take the leading position in the structure of mortality. Among the diseases of the cardiovascular system the leading position is occupied by coronary heart disease. One of the manifestations of coronary heart disease is acute coronary syndrome. In addition to endovascular treatment, dual antiplatelet therapy plays a key role in the treatment and prevention of acute coronary syndrome. Double antiplatelet therapy is a combination of acetylsalicylic acid and platelet P2Y12 receptor inhibitors. One of the first drugs from the group of P2Y12 receptor inhibitors is clopidogrel. It has been proven that the use of clopidogrel to date not always reduces the risk of development of thrombotic complications, of particular interest are the representatives of the "new" platelet P2Y12 receptor inhibitors. Such platelet P2Y12-receptor inhibitors include ticagrelor and prasugrel. The article considers in detail the issue of efficiency and safety of prasugrel use. The results of the studies allow to distinguish this drug as an effective inhibitor of P2Y12 platelet receptors in patients with acute coronary syndrome who have undergone percutaneous coronary intervention. Considering the pronounced antiplatelet effect of the drug, it should not be prescribed to patients with stroke and a history of transient ischemic attack. Prasugrel also should not be prescribed in a full dose to patients over 75 years old and patients weighing up to 60 kg. These studies showed that when the recommendations are followed, prasugrel demonstrates good results in reducing the frequency of cardiovascular events in patients with acute coronary syndrome and percutaneous coronary intervention. Separately, we can distinguish the effect of prasugrel on the development of stent thrombosis. So, in patients that underwent stenting, the use of prasugrel significantly reduced the frequency of confirmed stent thrombosis, which can also affect the development of undesirable cardiovascular events.